Water-Stability of Pelleted Fish Feeds Prepared from Non-Conventional Sources - W., Jayadev; W., Vishwanath (Fishery Technology, 2025)
Fish feed was formulated using easily available low cost material as protein source and the water stability of the formulated feed was tested. It was found that feeds with higher fat content had better stability in water.